SURVEI TINGKAT KEBUGARAN JASMANI PADA PEMAIN PERSATUAN SEPAKBOLA INDONESIA LUMAJANG - SEPTIAN NOSA, AGUNG SEPTIAN (Jurnal Prestasi Olahraga, 2013)
All football players should have good physical fitness, because football is a game which is played in ninety minutes, so that, it needs good physical fitness to play this game. The purpose of this research is to know about VO? Max level of the member on Indonesian Football Association of Lumajang. VO? Max is a measure of each individual players to generate the energy while endurance activity without excessive fatigue. This research used quantitative non experiment with descriptive quantitative model approach. This research used 22 subjects. Therefore, to determine the endurance of football players was used VO? Max level, through Multistage Fitness Test (MFT). The result of this research shows that the average VO? Max level of the member on Indonesian Football Association of Lumajang is 49.02 ml/ kgBB/ min. It means that this level is quite good.   Keywords              : Physical Fitness, VO2 Max, Indonesian Football Association of Lumajang